An introduction to the epidemiology and burden of urinary tract infections. (March 2019) - Medina, Martha; Castillo-Pino, Edgardo
Urinary tract infections (UTIs) are the most common outpatient infections, with a lifetime incidence of 50−60% in adult women. This is a narrative review aimed at acting as an introduction to the epidemiology and burden of UTIs. This review is based on relevant literature according to the experience and expertise of the authors. The prevalence of UTI increases with age, and in women aged over 65 is approximately double the rate seen in the female population overall. Etiology in this age group varies by health status with factors such as catheterization affecting the likelihood of infection and the pathogens most likely to be responsible. In younger women, increased sexual activity is a major risk factor for UTIs and recurrence within 6 months is common. In the female population overall, more serious infections such as pyelonephritis are less frequent but are associated with a significant burden of care due to the risk of hospitalization. Healthcare-associated UTIs (HAUTIs) are the most common form of healthcare-acquired infection. Large global surveys indicate that the nature of pathogens varies between the community and hospital setting. In addition, the pathogens responsible for HAUTIs vary according to region making adequate local data key to infection control. UTIs create a significant societal and personal burden, with a substantial number of medical visits in the United States every year being related to UTIs. European data indicate that recurrent infections are related to increased absenteeism and physician visits. In addition, quality of life measures are significantly impacted in women suffering from recurrent UTIs. Data suggest that nonantimicrobial prophylactic strategies offer an opportunity to reduce both the rate of UTIs and the personal burden experience by patients.